Archeointensity estimates of a tenth-century kiln: first application of the Tsunakawa–Shaw paleointensity method to archeological relics - Yu Kitahara; Yuhji Yamamoto; Masao Ohno; Yoshihiro Kuwahara; Shuichi Kameda; Tadahiro Hatakeyama (Earth, Planets and Space, 2018)
Abstract Paleomagnetic information reconstructed from archeological materials can be utilized to estimate the archeological age of excavated relics, in addition to revealing the geomagnetic secular variation and core dynamics. The direction and intensity of the Earth’s magnetic field (archeodirection and archeointensity) can be ascertained using different methods, many of which have been proposed over the past decade. Among the new experimental techniques for archeointensity estimates is the Tsunakawa–Shaw method. This study demonstrates the validity of the Tsunakawa–Shaw method to reconstruct archeointensity from samples of baked clay from archeological relics. The validity of the approach was tested by comparison with the IZZI-Thellier method. The intensity values obtained coincided at the standard deviation (1σ) level. A total of 8 specimens for the Tsunakawa–Shaw method and 16 specimens for the IZZI-Thellier method, from 8 baked clay blocks, collected from the surface of the kiln were used in these experiments. Among them, 8 specimens (for the Tsunakawa–Shaw method) and 3 specimens (for the IZZI-Thellier method) passed a set of strict selection criteria used in the final evaluation of validity. Additionally, we performed rock magnetic experiments, mineral analysis, and paleodirection measurement to evaluate the suitability of the baked clay samples for paleointensity experiments and hence confirmed that the sample properties were ideal for performing paleointensity experiments. It is notable that the newly estimated archaomagnetic intensity values are lower than those in previous studies that used other paleointensity methods for the tenth century in Japan.